Benefits of and Barriers to Male Involvement in Maternal Health Care in Ibanda District, Southwestern, Uganda - Bagenda, Fred; Batwala, Vincent; Orach, Christopher Garimoi; Nabiwemba, Elizabeth; Atuyambe, Lynn (Open Journal of Preventive Medicine, 2021)
Background: Male involvement in reproductive health care has been shown to have positive outcomes on the maternal and newborn’s health as they provide resources and make crucial decisions. However, male involvement in reproductive/ maternal health care in Uganda is still low. The objective of this study was to explore community perspectives on benefits and barriers to men’s involvement in maternity care in southwestern Uganda. Methods: The study was a cross-sectional, exploratory study, in Ibanda district, southwestern Uganda Data collection was collected in May 2020, using qualitative methods, narrative interviews and analyzed using a content-based approach. The sampling was done purposively and 18 narrative interviews were conducted. Results: Eighteen (18) narrative interviews were conducted at households of the participants. The identified benefits of male’s involvement in reproductive care services included family wellbeing and health, health care services utilization, health care worker motivation and community improvement and development. The barriers that emerged included individual and behavioral factors like ignorance/knowledge, responsibility, excessive alcohol consumption, laziness and lack of money. Family and extended family factors included trust and cooperation by the couple, fidelity issues, domestic violence and family perceptions. The environment, cultural and gender factors like misperceptions of male involvement, the cultural beliefs about the role of men in reproductive issues and the gender norms. The health care services factors included timing of the services the attitude of the health workers and the availability and access to the health services. Conclusions: The benefits of male involvement in maternal health care include family wellbeing and health, healthcare services utilization, health worker motivation and community improvement and prosperity. The barriers to male involvement in antenatal, delivery and postnatal care include individual and behavioral, family and extended family, environmental, cultural and gender and health care services factors. Therefore interventions to improve male involvement should focus on the individual, family, cultural, gender and health care services factors.
Keywords: Barriers; Benefits; Male Involvement; Antenatal; Skilled Delivery; Postnatal Care